1999
DOI: 10.1016/s0896-6273(00)80860-0
|View full text |Cite
|
Sign up to set email alerts
|

Reelin Is a Ligand for Lipoprotein Receptors

Abstract: A signaling pathway involving the extracellular protein Reelin and the intracellular adaptor protein Disabled-1 (Dab1) controls cell positioning during mammalian brain development. Here, we demonstrate that Reelin binds directly to lipoprotein receptors, preferably the very low-density lipoprotein receptor (VLDLR) and apolipoprotein E receptor 2 (ApoER2). Binding requires calcium, and it is inhibited in the presence of apoE. Furthermore, the CR-50 monoclonal antibody, which inhibits Reelin function, blocks the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
601
4
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 747 publications
(623 citation statements)
references
References 46 publications
10
601
4
2
Order By: Relevance
“…This hypothesis is supported by studies in transgenic animals showing ectopic accumulations of Dab1 in Reelin-, ApoER2-, and VLDLR-deficient mice (Rice and Curran, 2001;Trommsdorff et al, 1999). In-vitro studies showed that internalization of Reelin-ApoER2 complexes is required for endocytosis and proteasomal degradation of Dab1 (Bock et al, 2004;D'Arcangelo et al, 1999). A direct role of Reelin in APP processing is demonstrated by the increased co-immunoprecipitation of Dab1 with ApoER2 and APP and decreased Aβ production (Hoe et al, 2006a), indicating that reduced Reelin levels might favor the production of neurotoxic Aβ species.…”
Section: Discussionmentioning
confidence: 81%
“…This hypothesis is supported by studies in transgenic animals showing ectopic accumulations of Dab1 in Reelin-, ApoER2-, and VLDLR-deficient mice (Rice and Curran, 2001;Trommsdorff et al, 1999). In-vitro studies showed that internalization of Reelin-ApoER2 complexes is required for endocytosis and proteasomal degradation of Dab1 (Bock et al, 2004;D'Arcangelo et al, 1999). A direct role of Reelin in APP processing is demonstrated by the increased co-immunoprecipitation of Dab1 with ApoER2 and APP and decreased Aβ production (Hoe et al, 2006a), indicating that reduced Reelin levels might favor the production of neurotoxic Aβ species.…”
Section: Discussionmentioning
confidence: 81%
“…(27,(31)(32)(33) LRP8, as one of the cell-surface receptors for Reelin, functions as an important regulator of neuron migration in brain development. (34,35) Reelin signals through LRP8 or through very-low-density lipoprotein receptor (VLDLR), induces the interaction between LRP8 and adaptor protein Disabled-1 (Dab1) and tyrosine phosphorylation of Dab1, and further, results in the recruitment of phosphatidylinositol-3-kinase (PI3K) and GSK3b. (34,(36)(37)(38) Interaction between LRP8 and Reelin also initiates internalization of Reelin in the clathrin-mediated endocytosis pathway.…”
Section: Introductionmentioning
confidence: 99%
“…(34,35) Reelin signals through LRP8 or through very-low-density lipoprotein receptor (VLDLR), induces the interaction between LRP8 and adaptor protein Disabled-1 (Dab1) and tyrosine phosphorylation of Dab1, and further, results in the recruitment of phosphatidylinositol-3-kinase (PI3K) and GSK3b. (34,(36)(37)(38) Interaction between LRP8 and Reelin also initiates internalization of Reelin in the clathrin-mediated endocytosis pathway. (39) LRP8 single-knockout mice were grossly normal, but showed reduced male fertility and suffered accelerated cell death during normal aging 4,35 ; LRP8 and VLDLR double-knockout mice displayed disorganized neurons, and cortical lamination was affected in brain development.…”
Section: Introductionmentioning
confidence: 99%
“…39 Reelin serves a dual purpose in the mammalian brain: it is crucial to the correct cytoarchitecture of laminated structures during embryonic development 18,40 and modulates dendritic growth and synaptic plasticity at post-natal and adult stages. 41,42 These activities are, at least in part, mediated by binding to apolipoprotein E receptor 2 (ApoER2) and very low-density lipoprotein receptor (VLDLR), [43][44][45] resulting in phosphorylation of the intracellular adaptor protein protein disabled homolog 1 (DAB1). [46][47][48] Phosphorylated DAB1 activates several different signaling pathways involved in formation and plasticity of neuronal networks (for review, see ref.…”
mentioning
confidence: 99%